A High Postoperative Atropinic Burden is Associated with Postoperative Delirium in Elderly Patients with Hip Fracture: Results of the Prospective, Observational, ATROPAGE Trial - Ferré F; Piel-Julian ML; Tincres F; Ba C; Menut R; Ferrier A; Bosch L; Martin C; Labaste F; Montastruc F; Sommet A; Balardy L; et al. (Clinical Interventions in Aging, 2022)
Fabrice Ferré,1,* Marie-Léa Piel-Julian,2,* Francis Tincres,1 Cyndie Ba,1 Rémi Menut,1 Anne Ferrier,1 Laetitia Bosch,1 Charlotte Martin,1 François Labaste,1 François Montastruc,3 Agnès Sommet,3 Laurent Balardy,2,* Vincent Minville1,4,* 1Département d’Anesthésie-Réanimation et de Médecine Péri Opératoire, Centre Hospitalo-universitaire (CHU) de Toulouse, Toulouse, France; 2Service d’Oncogériatrie, Centre Hospitalo-universitaire (CHU) de Toulouse, Institut Universitaire du Cancer de Toulouse-Oncopole (IUCT-O), Toulouse, France; 3Laboratoire de Pharmacologie Médicale et Clinique, Centre Midi-Pyrénées de Pharmacovigilance, de Pharmacoépidémiologie et d’Informations sur le Médicament, Pharmacopôle Midi-Pyrénées, INSERM UMR 1027, CIC INSERM 1436, CHU Toulouse, Toulouse, France; 4RESTORE, UMR 1301 Inserm - 5070 CNRS - Université Paul Sabatier, Université de Toulouse, Toulouse, France*These authors contributed equally to this workCorrespondence: Fabrice Ferré, Hôpital Pierre-Paul Riquet, CHU Purpan, place du Dr Baylac, Toulouse, 31059, France, Tel +33 5 61 77 99 88, Email ferre.f@chu-toulouse.frBackground: Postoperative delirium frequently occurs in the elderly after hip fracture surgery and is associated with poor outcomes. Our aim was to identify a correlation between the atropinic burden (AB) due to drugs with clinical antimuscarinic effect and the occurrence of postoperative delirium.Methods: We carried out a prospective, monocentric, observational study including 67 patients over 65 years of age who underwent hip fracture surgery. The addition of the anticholinergic weight of each drug was calculated at different time points to distinguish the prehospital, intra- and postoperative part of the AB. A multivariate analysis was carried out to identify the explanatory variables associated with postoperative delirium.Results: Patients were 78 [71– 86] years old. The time from admission to surgery was 12 [12– 24] hours. The ADL and CIRS scores were 6 [5.5– 6] and 6 [4– 9], respectively. The total (prehospital plus intraoperative plus postoperative) AB was 5 [3– 9]. The incidence of postoperative delirium was 54% (36/67). The demographic characteristics were comparable between delirium and no delirium groups. Univariate analysis showed statistically significant differences between no delirium and delirium groups concerning the number of prehospital atropinic drugs, prehospital AB, the number of postoperative atropinic drugs, postoperative AB, in-hospital AB and the MMSE calculated on postoperative day 5. Using multivariate analysis, postoperative AB, but not pre- and in-hospital ABs, was associated with postoperative delirium with an odds ratio of 1.84 (95% CI: 1.25– 2.72; p = 0.002). A postoperative AB > 2 was associated with a postoperative delirium with an area under ROC curve of 0.73 (95% CI: 0.61– 0.83; p = 0.0001).Conclusion: Contrary to a prior exposure to atropinic drugs, a postoperative atropinic burden > 2 was associated with postoperative delirium in elderly patients with hip fracture. Postoperative administration of (new) antimuscarinic drugs is a precipitating factor of delirium that could be avoided.Keywords: post-operative, anesthesia, atropinic burden, hip fracture, delirium